2016
DOI: 10.5812/archneurosci.39263
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Nerve Stimulation for Major Depressive Disorder: An Updated Systematic Review

Abstract: Context: Trigeminal nerve stimulation (TNS) is a promising non-invasive brain stimulation intervention. The TNS has been proposed for major depressive disorder (MDD) with auspicious results. The aim of this study was to review the literature on TNS for MDD. Evidence Acquisition: Systematic review, using MEDLINE and EMBASE, of first articles available until 22nd of April 2016. Results: We included seven studies; six of them were open-label studies and one sham-controlled randomized double-blinded trial. Most st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Increased firing of VP neurons is also found in depression and silencing of VP neurons can ameliorate depressive-like behaviors ( Knowland et al 2017 ). Increased salt intake driven by liking of salt ( Hayes et al 2010 ; Pilic et al 2020 ) may lead to TN nerve stimulation ( Simon et al 2008 ; Bigiani, 2020 , 2021 ) which ameliorates depression ( Schrader et al 2011 ; Cook et al 2013 ; Paulino Trevizol and Cordeiro 2016 ; Generoso et al 2019 ) and anxiety ( Trevizol et al 2015 ; Freire et al 2020 ). Liking of salty foods can be reduced through exposure to lower sodium diets ( Riis et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased firing of VP neurons is also found in depression and silencing of VP neurons can ameliorate depressive-like behaviors ( Knowland et al 2017 ). Increased salt intake driven by liking of salt ( Hayes et al 2010 ; Pilic et al 2020 ) may lead to TN nerve stimulation ( Simon et al 2008 ; Bigiani, 2020 , 2021 ) which ameliorates depression ( Schrader et al 2011 ; Cook et al 2013 ; Paulino Trevizol and Cordeiro 2016 ; Generoso et al 2019 ) and anxiety ( Trevizol et al 2015 ; Freire et al 2020 ). Liking of salty foods can be reduced through exposure to lower sodium diets ( Riis et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there may be salt taste-associated changes to neurotransmitters, impacting mental health. High salt concentrations may modulate mood through stimulation of the trigeminal nerve (TN) ( Simon et al 2008 ; Bigiani 2020 , 2021 ) which also has an ameliorating effect on symptoms of depression ( Schrader et al 2011 ; Cook et al 2013 ; Paulino Trevizol and Cordeiro 2016 ; Generoso et al 2019 ) and anxiety ( Trevizol et al 2015 ; Freire et al 2020 ). Other studies have demonstrated increased neuronal activity in the ventral pallidum (VP), the center of hedonic liking in the brain ( Smith et al 2009 ; Root et al 2015 ), when salt liking increases under sodium depletion ( Tindell et al 2006 ) and in depression ( Knowland et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Trigeminal nerve stimulation is a noninvasive neuromodulation technique that stimulates the peripheral cutaneous endings of the trigeminal nerve on the scalp, there by modulating the associated brain areas linked to trigeminal nerve nucleus. [44][45][46] Trigeminal nerve stimulation is safe, with no major side effects. 46 Existing evidence supports the potential role of trigeminal nerve stimulation in managing major depressive disorder, posttraumatic stress disorder, attention-deficit hyperactivity disorder (ADHD) and epilepsy.…”
Section: Trigeminal Nerve Stimulationmentioning
confidence: 99%
“…[44][45][46] Trigeminal nerve stimulation is safe, with no major side effects. 46 Existing evidence supports the potential role of trigeminal nerve stimulation in managing major depressive disorder, posttraumatic stress disorder, attention-deficit hyperactivity disorder (ADHD) and epilepsy. [44][45][46][47][48]…”
Section: Trigeminal Nerve Stimulationmentioning
confidence: 99%
See 1 more Smart Citation